Developments in anti-complement therapy; from disease to clinical trial. (October 2018) - Harris, Claire L.; Pouw, Richard B.; Kavanagh, David; Sun, Ruyue; Ricklin, Daniel
Highlights: Complement plays a key role in pathogenesis of inflammatory and autoimmune disease. Numerous drugs are in clinical development for diseases of the kidney, eye and vasculature. We present validation for anti-complement therapy in indications involving these tissues. We describe the successes and challenges associated with therapeutic modulation of complement in these indications. Abstract: The complement system is well known for its role in innate immunity and in maintenance of tissue homeostasis, providing a first line of defence against infection and playing a key role in flagging apoptotic cells and debris for disposal. Unfortunately complement also contributes to pathogenesis of a number of diseases; in some cases driving pathology, and in others amplifying or exacerbating the inflammatory and damaging impact of non-complement disease triggers. The role of complement in pathogenesis of an expanding number of diseases has driven industry and academia alike to develop an impressive arsenal of anti-complement drugs which target different proteins and functions of the complement cascade. Evidence from genetic and biochemical analyses, combined with improved identification of complement biomarkers and supportive data from sophisticated animal models of disease, has driven a drug development landscape in which the indications selected for clinical trial cluster in three 'target' tissues: the kidney, eye and vasculature. While the disease triggers may differ, complement activation and amplification is a common feature in many diseases which affect these three tissues. An abundance of drugs are in clinical development, some show favourable progression whereas others experience significant challenges. However, these hurdles in themselves drive an ever-evolving portfolio of 'next-generation' drugs with improved pharmacokinetic and pharmacodynamics properties. In this review we discuss the indications which are in the drug development 'spotlight' and review the relevant indication validation criteria. We present current progress in clinical trials, highlighting successes and difficulties, and look forward to approval of a wide selection of drugs for use in man which give clinicians choice in mechanistic target, modality and route of delivery.